Rhizoecus colombiensis Ramos & Caballero, a new species of hypogeal mealybug (Hemiptera: Coccomorpha: Rhizoecidae) and a key to the species of Rhizoecus from Colombia - Ramos-Portilla, Andrea Amalia; Caballero, Alejandro (Zootaxa, 2016)
A new species belonging to Rhizoecus Künckel d’Herculais (Hemiptera: Coccomorpha: Rhizoecidae) is described, with hosts and distribution data in the New World. A dichotomous and illustrated key for the twelve species of Rhizoecus recorded from Colombia is presented.